Liquidity traps, capital flows - Sushant Acharya; Julien Bengui (Federal Reserve Bank of New York, 2016)
This paper explores the role of capital flows and exchange rate dynamics in shaping the global economy's adjustment in a liquidity trap. Using a multi-country model with nominal rigidities, we shed light on the global adjustment since the Great Recession, a period when many advanced economies were pushed to the zero bound on interest rates. We establish three main results. First, when the North hits the zero bound, downstream capital flows alleviate the recession by reallocating demand to the South and switching expenditure toward North goods. Second, a free capital flow regime falls short of supporting efficient demand and expenditure reallocations and induces too little downstream (upstream) flows during (after) the liquidity trap. And third, when it comes to capital flow management, individual countries' incentives to manage their terms of trade conflict with aggregate demand stabilization and global efficiency. This underscores the importance of international policy coordination in liquidity trap episodes.
Keywords: E52; F32; F38; F42; F44; 330; capital flows; international spillovers; liquidity traps; uncovered interest parity; capital flow management; policy coordination; optimal monetary policy